Usaha Mikro Kecil Menengah Sebagai Sarana Untuk Meningkatkan Pendapatan Ekonomi Lokal - Syamsul Anwar; Syafaatul Hidayati; Kharisma Danang Yuangga (Program Studi Pendidikan Ekonomi Universitas Pamulang, 2021)
This study aims to raise micro and small businesses to improve the regional economy. This study understands to understand the owners of micro, small and medium enterprises, their input to the local economy in terms of employment, profits, and their ability to bring rupiah out into the local economy. As such, they qualify as significant providers of a society's economic growth. A key element in the development of a healthy society lies in the strength and diversity of its local economy. The data analysis technique used in this research is a research approach based on the nature of the research problem, the experience of the researcher and the research audience. The key to success in developing these relationships is that institutions such as the Center for Small Micro and Medium Enterprises Development and vocational and technology programs are carried out through mentoring programs and support the efforts made. In the end, the local economy is able to provide consistent economic growth. The output of the research is a journal to patch up the value of Jafung's kum.